Kesejahteraan Subjektif pada Pemulung: Tinjauan Sosiodemografi - Sarah Hafiza; Marty Mawarpury (Gadjah Mada Journal of Psychology (GamaJoP), 2019)
Subjective wellbeing is a negative or positive assessment of the experience experienced in all aspects of life. The purpose of this study was to identify the subjective welfare level of scavengers based on sociodemography. Using a quantitative approach with survey design methods and with incidental sampling techniques, the sample in the study involved 87 scavengers composed of 41 men and 46 women, aged 17-55 years, and domiciled in Banda Aceh. Subjective prosperity was measured using Satisfaction with Life Scale (SWLS) and Scale of Positive and Negative Experience (SPANE). The analysis methods used were descriptive statistics and chi square test for independent. The result of chi square statistic analysis showed that there was no correlation between subjective welfare of the scavengers in sociodemographic group (gender p > 0.05; age p > 0.05; last education p > 0.05; marital status p > 0.05; income p > 0.05). The result of descriptive analysis showed that the dominant research subjects were at high subjective well-being level (58 subjects or 66,7%).